La vía igualmente satisfactoria al proceso de amparo: implicancias del precedente Elgo Ríos en la pretensión de reposición de trabajadores del sector privado - Osorio Véliz, Rosa Valeria (2015)
This article analyzes the content of the judgment Elgo Rios, to see if really that judgment represents a change of direction before the criteria handled by the Constitutional Court. This will explain the implications of procedural rules implemented for the recruitment in the private system over the previous precedent governing the origin of labor protection, that is, the judgment on the record 206-2005-PA, the precedent Baylon.